A dictionary of writers and their works - Cox, Michael (Oxford University Press, 2001)
A quick-reference guide to authors and their works. The focus is on the general canon of British literature from the fifteenth century to the present. There is also some coverage of non-fiction such as biographies, memoirs, and science, as well as inclusion of major American, Commonwealth, and other foreign writers